STIMULASI DAYA INGAT DAN FOKUS ANAK PADA MASA EMAS DI TK TELAGA HIKMAH - Apriliani, Riska; Loka, Novita (I'tibar: Jurnal Pendidikan Islam Anak Usia Dini, 2025)
The golden age of early childhood is a critical period for the development of memory and focus, which play a vital role in children's cognitive abilities. This study explores strategies for stimulating memory and focus at Telaga Alhikmah Kindergarten using a comprehensive approach. The research employed qualitative methods with a field research approach, involving observations, in-depth interviews, and document analysis with the principal, teachers, students, and parents. Data were analyzed using the interactive model of Miles and Huberman, with triangulation ensuring data validity. The findings indicate that various stimulation methods, such as educational games, audiovisual media, mindfulness techniques, and memory games, are highly effective in enhancing children's memory and focus. Differentiated and personalized stimulation approaches proved optimal in meeting the unique characteristics of each child. This study highlights the importance of collaboration among teachers, parents, and educational institutions in creating an environment that supports comprehensive cognitive development in children